Penerapan Budaya Kaizen untuk Meningkatkan Motivasi Berwirausaha Dikalangan Mahasiswa - Darham Wahid; Yudhi Novriansyah; Supriyati Supriyati; Herawati Herawati; Khairun A Roni (Lembaga Pengembangan Kinerja Dosen, 2025)
In order to enhance the entrepreneurial spirit among the younger generation, especially among students, the Faculty of Economics teaching staff, supported by the Research and Community Service Institute (LPPM) of Muara Bungo University, conducted Community Service activities with the theme